Political identification in Europe : community in crisis? - Machin, Amanda; Meidert, Nadine (Emerald Publishing Limited, 2021)
In recent years, Europe has been buffeted by a series of contested crises that seemingly undermine and overwhelm its institutions and ideals: the economic shocks of 2008, the open disputes over migration, the political uncertainty generated by Brexit and the inroads made by various populist and nationalist parties into government. These interconnected trends have exposed the myth of a cohesive European community. Instead, what can be witnessed is the polarization, fragmentation and displacement of the European public sphere. At the very least, both the perceptions and realities of these crises and the reactions to them have disrupted established patterns of identity and instituted new ones. The emergent discourses of austerity, security, populism and anti-populism, for example, are all rooted in a transforming political landscape. In this context, a re-examination of what it means to belong in and to Europe today is required. By presenting a rich and wide-ranging collection of the latest interdisciplinary scholarship that carefully unpacks the complex dimensions of European identification, this book considers the contemporary concerns and possibilities for political identification in Europe. Written by scholars from across the continent, this volume presents an enriching insight into the European socio-political condition. Each chapter offers a distinct perspective and detailed analysis of a different aspect of 'identity'. Together, these chapters constitute an invaluable resource for approaching the challenges facing Europe today.
Includes index.
Keywords: Political sociology -- Europe.; Europe -- Politics and government -- 21st century.; Political Science, World -- European.; Regional government policies.; elektronické knihy; electronic books